RANCANG BANGUN ALAT PENGUKUR DAN PENGATUR SUHU RUANGAN GREENHOUSE TANAMAN MELON HIDROPONIK BERBASIS IOT - Adam Kurniawan; M. Dewi Manikta Puspitasari; Miftakhul Maulidina; Elsanda Merita Indrawati (Nusantara of Engineering (NOE), 2026)
Agriculture has experienced developments, especially in the horticultural sector that has high economic value, such as the melon business cultivated through Greenhouses, but the indoor temperature is higher than outside due to the greenhouse effect and the absence of a temperature control system in the Greenhouse. The purpose of this study is to determine the design and working system of a hydroponic melon temperature measuring and regulating device in an IoT-based Greenhouse in stabilizing the temperature. The research model used is a "prototyping model" because in the process of developing a temperature control device, it requires stages of making an initial prototype, testing, until the system is refined in stages, in data collection the researcher conducted field observations, documentation, automatic recording of the system from the DS18B20 sensor readings and sent the data to the webserver via an ESP32 Wi-Fi connection as well as interviews with partners who are members of the melon farmer group in Ngadiluwih Village, Kediri. The results of this research show that monitoring and regulating temperature on the IoT dashboard (Blynk) can be done in real-time using a DS18B20 temperature sensor, ESP32 microcontroller, heater lamp, and AC fan. The tools studied and tested can maintain the temperature in the Greenhouse within the ideal range (between 25°C - 30°C) automatically with fast and stable responsiveness.